Legal Dynamics in the Digital Era: Navigating the Impact of Digital Transformation on Indonesian Society - Nainggolan, Bernard (Law Development Journal, 2023)
Legal philosophy provides an important foundation in understanding the basic principles of law, such as justice, freedom and responsibility. By taking these ethical values into account, legal rules can be formulated that ensure the protection of society's rights and interests in the face of rapid technological change. Through an in-depth study of primary and secondary legal sources, this research describes legal phenomena related to digital transformation in Indonesia by utilizing primary legal materials, especially related laws, to understand the legal basis on which laws are formed in the face of digital transformation. Legal philosophy plays an important role in articulating the concept of justice in the legal system. This concept is a guide for making laws that must develop along with the development of society. In the context of digital technology development in Indonesia, the importance of progressive regulations is crucial. These regulations must provide clear guidelines for the use of digital technology to ensure that the benefits can be obtained while the negative impacts can be minimized. Thus, legal philosophy becomes an important basis in creating legal conditions that are in line with current developments. Legal philosophy brings a deep understanding of the concept of justice and how this concept should be reflected in the applicable legal system. By considering philosophical values and principles, it is hoped that the legal system can achieve nobler goals and provide protection and prosperity for the entire community.